Biomechanical Comparison of Lumbar Motion Unit Stability Following Posterior Instrumentation with Facet Spacers and Facet Screws - Mu-Yi Liu; Tsung-Ting Tsai; Lih-Huei Chen; Wen-Huang Liang; Po-Liang Lai; Ching-Lung Tai (Journal of Medical and Biological Engineering, 2020)
Purpose Lumbar posterior instrumentation for facet stabilization has become popular for the treatment of lumbar instability. The present study investigated and compared facet stabilization following lumbar posterior instrumentation with facet spacers and facet screws using porcine lumbar spines. Methods Eighteen L5–L6 lumbar motion units (LMUs) of the porcine spines were randomly divided into three groups (un-instrumented, facet-spacer and facet-screw). In the un-instrumented group (control), all ligamentous structures were preserved. In the facet-spacer group, two facet spacers were inserted into the joint spaces of the bilateral upper and lower facets. In the facet-screw group, two cannulated screws were used to transfix the bilateral upper and lower facets. With the use of a material testing machine, a gradually increasing moment of up to 6000 N-mm was generated in flexion, extension, lateral bending and torsion motions to compare facet stabilization among the groups. Results The facet-spacer group was significantly stiffer than the facet-screw group in extension ( p = 0.013), whereas the facet-screw group was significantly stiffer than the facet-spacer group in axial rotation ( p = 0.004). No statistically significant differences were observed between the two fixation techniques in flexion ( p = 0.284) and lateral bending ( p = 0.085). Conclusion Both facet-spacer and facet-screw fixation techniques significantly improve stability in a single LMU. Facet-spacer fixation provided better stabilization in extension, while facet-screw fixation provided better stabilization in axial rotation.